Alternative Strategies to Achieve Cardiovascular Mortality Goals in China and India: A Microsimulation of Target- Versus Risk-Based Blood Pressure Treatment. Issue 9 (1st March 2016) - Basu, Sanjay; Yudkin, John S.; Sussman, Jeremy B.; Millett, Christopher; Hayward, Rodney A.
Abstract : Background—: The World Health Organization aims to reduce mortality from chronic diseases including cardiovascular disease (CVD) by 25% by 2025. High blood pressure is a leading CVD risk factor. We sought to compare 3 strategies for treating blood pressure in China and India: a treat-to-target (TTT) strategy emphasizing lowering blood pressure to a target, a benefit-based tailored treatment (BTT) strategy emphasizing lowering CVD risk, or a hybrid strategy currently recommended by the World Health Organization. Methods and Results—: We developed a microsimulation model of adults aged 30 to 70 years in China and in India to compare the 2 treatment approaches across a 10-year policy-planning horizon. In the model, a BTT strategy treating adults with a 10-year CVD event risk of ≥10% used similar financial resources but averted ≈5 million more disability-adjusted life-years in both China and India than a TTT approach based on current US guidelines. The hybrid strategy in the current World Health Organization guidelines produced no substantial benefits over TTT. BTT was more cost-effective at 205 to 272/disability-adjusted life-year averted, which was 142 to 182 less per disability-adjusted life-year than TTT or hybrid strategies. The comparative effectiveness of BTT was robust to uncertainties in CVD risk estimation and to variations in the age range analyzed, the BTT treatment threshold, or rates of treatment access, adherence, or concurrent statin therapy. Conclusions—: In model-based analyses, a simple BTT strategy was more effective and cost-effective than TTT or hybrid strategies in reducing mortality. Abstract : Supplemental Digital Content is available in the text.